The psychosocial contract: Its nature and effects fro Greek industry - Nicolaou-Smokovitis, L. (The Greek Review of Social Research, 1976)
The basic focus of this paper lies in the definition of the «psychosocial contract» as a new concept in organization theory, and the discussion of its potential theoretical and practical usefulness. This concept derived out of a research study in the Greek industry and is supported by current organization theory and traditional political philosophy. The basic problem of the Greek study centered around the topic of success of industrial firms within the Greek economy, success being defined in terms of a systems-effectiveness model. The findings, while supporting previous contingency theories developed in other Western industrial settings, further extended them by adding «Social Accountability » as a major predictor of organizational success. A conceptual model, supported by the Greek data, provided an adequate explanation of differences in success among Greek industrial firms, and suggested a workable «psychosocial contract.» The psychosocial contract, as a theoretical construct, helped to explain the Greek data more conveniently than would be possible without it.